Strengthening Student Character Education Based on School Culture at Bissappu Public Junior High School 1, Bantaeng Regency - Suardi Suardi; Arni Yusnita; Muhajir Muhajir (JED (Jurnal Etika Demokrasi), 2022)
The research problem is the cultivation of student character which still needs reinforcement from the school. The purpose of this study was to examine the Strengthening of School Culture-Based Student Character Education at Bissappu Public Junior High School 1, Bantaeng Regency. The research method using mixed methods focuses on collecting, analyzing, and mixing quantitative and qualitative data in a single or follow-up research, so that it can provide a better understanding or answer to the research problem compared to using one of them. Based on the results of research through observation, interviews, documentation and questionnaires, the implementation of character strengthening through school culture in Bissappu 1 Public Junior High School is carried out through (a) determining the main values of strengthening character education (b) compiling a daily/weekly schedule for strengthening character education (c) developing school culture. The implementation of character education based on school culture in learning has been carried out in schools.